Hydroalcoholic Extract of Glycyrrhiza glabra Linn. Attentuates Chronic Fatigue Stress Induced Behavioral Alterations in Mice. - Trivedi, Rahul (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT The present study evaluates the protective effect of hydroalcoholic extract of Glycyrrhiza glabra on chronic fatigue stress (CFS) induced behavioral alterations. The exposure of mice to chronic fatigue stress for 15 days demonstrated an increased immobility time, increased anxiety, impaired memory, reduction in muscle co-ordination, reduced activity and increased pain perception. The altered behavioral parameters were attenuated significantly by the treatment of Glycyrrhiza glabra (100 and 200 mg/kg p.o) comparable to fluoxetine (10 mg/kg, i.p.). The study concludes that Glycyrrhiza glabra could be used as an alternative to conventional medicines for the treatment of chronic fatigue stress.